Modulation of Immune Responses by Exosomes Derived from Antigen-Presenting Cells (Indo-American Journal of Life Sciences and Biotechnology, 2023)
The mediating role of exosome-mediated signalling in the inflammatory response is significant. Exosomestransport a wide variety of biomacromolecules, such as proteins, lipids, coding and non-coding RNAs, and avariety of lengths of RNA, to the cells they infect in order to carry out their biological or pathological activities.Therapeutic effects may be conferred by attenuating or boosting the immune response via exosomes released byantigen-presenting cells. In order to modify T cell responses specific to antigens, exosomes are essential fortransporting and displaying functional major histocompatibility peptide complexes. Dendritic cell (DC) exosomeshave immunostimulatory capabilities and have been investigated for use in cancer treatment due to their abilityto stimulate T and B cells. In animal models of several inflammatory diseases, exosomes produced bymacrophages and DCs have immunosuppressive characteristics that alleviate inflammation. Research onexosomes produced by dendritic cells (DCs) and macrophages (macrophages) is the primary emphasis of thisreview, which aims to shed light on the protective function of exosomes in reducing inflammation and enhancingthe immune response.